KEBIJAKAN PEMBERDAYAAN PEREMPUAN ( KAJIAN TENTANG UPAYA PEMBERDAYAAN PEREMPUAN DI DESA BULUH CINA KECAMATAN SIAK HULU) - Asrida, Wan; ', Erman M (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
The Buluh Cina Village, one of eight villages located in the Distric Siak Hulu-Kampar Regency, is famous for its abundant natural resources. However, this villagehas high unemployement women (60 % ) and low educated women; thus it requiresconsiderable efford by village goverment to empower them through policy, programmeand activities, which could be realized by women.The women then could participate inthe village development and assist the improvement of their family economy.Key word : policy, empowerment, women.